Implementation of Academic Cultural Values in Student Campus Life: A Study - Nurmalina Nurmalina; Mesiono Mesiono; Hasan Asari (Newinera Publisher, 2026)
This study examines the implementation of academic cultural values in student campus life at the State Islamic Institute (IAIN) Takengon, Aceh Tengah, Indonesia. Academic culture plays an important role in shaping students’ attitudes, behaviors, and intellectual development within higher education institutions. This research aims to analyze how academic norms, academic activities, and academic works are implemented among students in order to create a productive academic environment. The study employed a qualitative research design with a phenomenological approach. Data were collected through in-depth interviews, non-participant observations, and document analysis involving university leaders, faculty members, and students. The data were analyzed using the interactive model of Miles and Huberman, which includes data condensation, data display, and conclusion drawing. The findings reveal that the implementation of academic culture at IAIN Takengon is carried out through several strategies, including the socialization of academic regulations through student orientation programs, the role modeling of academic behavior by lecturers and university leaders, and the integration of academic norms in daily learning activities. In addition, the development of academic literacy, the ethical use of digital technology and social media, and the promotion of academic activities such as seminars, workshops, research collaboration, and student organizational involvement contribute to strengthening academic culture among students. Institutional support, adequate academic facilities, and active participation of lecturers and students were identified as key factors supporting the development of academic culture, although challenges related to student motivation and engagement remain.